(3GdHjQhbQGWjI ai GdEOGQI GdeMdjI (B/s - (3eMeO eMeO YHOGdhgGHs; (3eGLO QGZH GdMdhs; (3LGeYI GdEScfOQjIs (3cdjI GdMbhbs ((3GdEScfOQjI(B:s (3cdjI GdMbhb(B-(3LGeYI GdEScfOQjI,s, 2003)
(3dbO JfGhdfG aj gPG GdHMK HYV ef GdLhGfH GdSdHjI aj CYeGd GdEOGQI GdeMdjI hhVYfG dgG HYV GdMdhd GdYedjI , hCf cfG fQi Gfg jUYH GdJZjjQ eGde Jcf gfGc EQGOI LGOI hUGObI Ydi GdJZjjQ (B.(3y Ef Gddg dGjZjQ eG Hbhe MJi jZjQhG eG HCfaSge y(B. (3hbdfG Gfg jLH Cf jchf GdJZjjQ aj GdLhgQ bHd GdTcd hGf jchf GdGgJeGe HGdaQO bHd GdBdI , Gi HeTZd GdBdI hgh GdehXa , MjK JHjjf ef GdHMK YO hVY GdehXa aj Gi GYJHGQ HMjK jchf GdgOa efg gh GdEUdGM , aYdi SHjd GdeKGd (B: (3dG jhLO JfGSH GdHJI Hjf eG jJbGVGg GdehXa ef GLQ hHjf eJWdHGJ GdMjGI GdaYdjI(B. - (3dG jhLO fTGW GLJeGYj aYdi dEYGdI GdehXa aj MGdI GdchGQK Hd gfGc CfTWI JQajgjI JSJgdc hdG JVja(B. - (3dG JhLO fbGHI aYdjI ddehXajf ddeWGdHI HGdMbhb Ch Gdhbha Edi LGfH GdehXa aj HYV eG jWQC Ydjg ef eMf hchGQK(B. - (3jJe fbd HYV GdehXajf Edi efGWb jUYH ajgG GdhUhd HGdehGUdGJ GdYGOjI Ohf GdfXQ Edi eG jYGfjg ef eTbI eGOjI hUMjI(B. - (3OGFeG jfXQ Edi GdObI aj ehGYjO GdMVhQ hGdGfUQGa Ohf GdfXQ Edi eG Hjf Pdc ef hbJ (B. 6- (3GdJSdSd GdQbGHj aj MGLI Edi CYGOI GdfXQ deG jJNddg ef hLhO HYV CaQGO dgG eUGdM eJHGOdI eY HYV ehXaj GdEOGQI GdeMdjI hHGdCNU GdbjGOjI ajgG (B.s
(3QSGFd fSNI efaQOIs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdEScfOQjI, cdjI GdMbhb, bSe GdbGfhf GdYGe (B2003s
(3jTJed Ydi EQLGYGJ HjHdjhLQGajI(B: (3UaMI (B563-586s
Keywords: (3GdGOGQI GdeMdjIs; (3GdGOGQg GdeMdjg s; (3GdHjQhbQGWjg s; (3GdfaGb GdGOGQi s; (3GdHWGdg GdebfYg s; (3GdbjGOg GdGOGQjg s; (3GdGSJZdGd GdhXjai s; (3GdeLGdS GdTYHjg GdeMdjg s; (3GdeTQhY GdYGes -- (3LGeYI GdEScfOQjIs -- (3GdbGfhf GdYGes